The Occurrence of Aflatoxin M1 in Milk, soft cheese and yoghurt in Baghdad Province by Using ELISA Test: Najim Hadi Najim and Huda Nsaif Jasim - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2014)
Milk and dairy products are fundamental components in the human diet and may be the principle way for entrance of Aflatoxin M1 (AFM1) in to the human body. All milk and dairy products samples were tested for the occurrence of AFM1 by the competitive ELISA technique. Out of 32 bovine raw milk samples that were collected from eight villages around Baghdad province, 32 samples (100 %) were contaminated with AFM1 ranging from 0.15 to 86.96ng/kg with mean value of 42.37±26.07 ng/kg, of which 17 samples were contaminated with concentrations < 50 ng/kg and 15 samples exceeded the maximum acceptable level of AFM1 in milk (50 ng/kg) imposed by the European legislation. The raw milk samples belonged to animals fed with composite and stored fodder as in Althahab Alabiadh, Radhwaniya and Fadhaliya villages had higher significantly AFM1 concentrations over all the other five villages (Grazing feed). All 32 (100%) locally produced soft white cheese samples analyzed were contaminated with AFM1 ranging from 31.84 to 89.44 ng/kg with the mean value of 59.92±17.03 ng/kg. Out of 32 locally produced yoghurt samples analyzed, 32 samples (100%) were contaminated with AFM1 ranging from 0.16 to 42.74 ng/kg with the mean value of 16.92±11.55 ng/kg. Thirty samples (100%) of the examined 30 imported UHT milk samples that were collected from different commercial companies in the province of Baghdad presented significantly high contamination level with AFM1 that were found to range from 0.18 to 85.66 ng/kg.